The demigod diaries [compact disc, unabridged] - Riordan, Rick (Riordan, Rick. Heroes of Olympus., 2012)
Four short stories plus original art, interviews, puzzles, and games, reveal new insights into the world of Percy Jackson and the other heroes of Olympus.